ASSESSMENT OF THE CURRENT SPATIAL-TEMPORAL VARIATIONS OF PH ON THE SURFACE WATERS OF KUALA PERLIS, PERLIS - Aimie Rifhan Hashim; Sharir Aizat Kamaruddin; Khairul Naim Abd.Aziz; Jamil Tajam; Faeiza Buyong; Anisah Lee Abdullah; Tun Mohd Firdaus Azis; Anastacia Anscelly, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
This research aims to assess the spatial-temporal pH variations on the surface water of Kuala Perlis, Perlis. The sampling points were determined and recorded using the Global Positioning Systems (GPS) in December 2021. A total of five sampling points for each morning, afternoon, and evening period were established, and the pH meter readings were recorded. The analysis of variance (ANOVA) was set at 0.05 to determine the significant difference in the spatial-temporal mean pH readings using the Statistical Package for the Social Sciences (SPSS) version 26. The research found that the pH readings were 6.98 – 7.24, 6.76 -7.41, and 6.58 – 7.54 for the morning, afternoon, and evening periods. The research also found no significant difference in the mean pH readings with respect to temporal variations (> .05). However, the research found a significant difference in pH readings (p< .05) concerning spatial variations. The local government and non-government bodies can utilize the output of this research to monitor river acidification processes and the social-economic development of this area.